Antiseptic therapy with a polylacticacid-acetic acid matrix in burns - Ryssel, Henning; Gazyakan, Emre; Germann, Günter; Hellmich, Susanne; Riedel, Katrin; Reichenberger, Matthias; Radu, Christian Andreas (Wound repair and regeneration, 2010)
Bacterial colonization and infection are still the major causes of delayed healing and graft rejection following burns and they are furthermore the basis for second and third hit sepsis. Topical treatment is necessary to reduce the incidence of burn wound infection. Silver sulphadiazine (SD-Ag) is a frequently used microbicidal agent. However, this treatment causes adverse reactions and side-effects. Additionally, in recent years multiresistant bacteria, which have not been treated sufficiently, are on the rise. On the basis of experimental data and clinical application of a polylacticacid-acetic acid matrix, we performed this study to establish the effectiveness of the antiseptic therapy with the topical application of a polylacticacid-acetic acid matrix to provide an alternative method for burn treatment, using SD-Ag as a reference. Twenty patients with IIb° or III° burns from the Plastic Surgery and Burns Unit were treated within a matched pair comparative setting. One burned area was treated with SD-Ag, the other corresponding area with the polylacticacid-acetic acid matrix. All patients underwent a necrectomy 4-5 days after the trauma. The excised burned skin was sent to our microbiological laboratory to determine the different bacteria per gram in this tissue. Despite the number of 20 patients, statistical significance was not achieved, there were tendencies to a better antiseptic effectiveness of the polylacticacid-acetic acid matrix. These results suggest that the polylacticacid-acetic acid matrix should be studied in greater depth and could be used as a valid alternative for the topical treatment of burns, as it is equivalent or even more effective than SD-Ag.